Dendrimer-activated surfaces for high density and high activity protein chip applications - Pathak, Srikant (Langmuir : the ACS journal of surfaces and colloids, 2004)
Highly functional Si and glass surfaces for protein immobilization have been prepared by a facile activation of native surface silanol groups. Poly(propyleneimine) dendrimers of generations 1-5 were immobilized onto the surface using a facile room-temperature coupling procedure that involved activation of native silanol groups of glass using 1,1'-carbonyldiimidazole under anhydrous conditions. The dendrimer-coated surfaces were used to immobilize proteins and were characterized with respect to surface loading and activity. A number of different chemical, physical, and biochemical techniques including contact angle measurement, ellipsometry, and fluorescence microscopy were used to characterize the resulting surfaces. Increasing the dendrimer generation past G-3 led to increased surface amine content, immobilized protein concentration, and the activity of immobilized alkaline phosphatase (used as a test system). Very high activity of the immobilized proteins in the case of higher generation (G-4 and G-5) dendrimers led us to conclude that such an approach has true potential for creating highly functional surfaces for protein chip applications